2008
DOI: 10.1155/2008/509459
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Budesonide in the Treatment of Autoimmune Hepatitis in Canada

Abstract: In Canada, budesonide has been successfully used in seven of nine patients with autoimmune hepatitis who were either intolerant to prednisone and azathioprine or prednisone-dependent. No adverse effects were reported with budesonide. Budesonide is potentially a valuable treatment option for AIH patients refractory or intolerant to standard therapy, and is deserving of further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 43 publications
(51 reference statements)
0
29
0
1
Order By: Relevance
“…Among the different autoimmune diseases, the risk of developing RA is maximum [20]. Smoking affects the onset of RA at different level -(1) age: onset at young age in smokers [21], (2) sex: risk higher in men [20], (3) abundance: 2.4 times more risk in younger smokers [22], (4) duration of smoking: risk of developing RA in current, former and even 20 years after smoking cessation [23]. Cigarette smoking is mostly related with rheumatoid factor (RF) and anti-cyclic citrullinated protein (anti-CCP) antibody seropositivity [24].…”
Section: Different Autoimmune Diseases Triggered By Smokingmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the different autoimmune diseases, the risk of developing RA is maximum [20]. Smoking affects the onset of RA at different level -(1) age: onset at young age in smokers [21], (2) sex: risk higher in men [20], (3) abundance: 2.4 times more risk in younger smokers [22], (4) duration of smoking: risk of developing RA in current, former and even 20 years after smoking cessation [23]. Cigarette smoking is mostly related with rheumatoid factor (RF) and anti-cyclic citrullinated protein (anti-CCP) antibody seropositivity [24].…”
Section: Different Autoimmune Diseases Triggered By Smokingmentioning
confidence: 99%
“…Due to the 15-fold higher affinity of budesonide to glucocorticoid receptors, it can be a second choice of prednisolone for induction and remission for the patients without the effect of cirrhosis [35]. This type of steroid has tested to give encouraging results with response rate of 80% in treatment-naive and non-responders to the standard ones [22,36]. Other interesting treatment strategy consists of different antibiotics like cyclosporine A.…”
Section: Treatments For Autoimmune Hepatitismentioning
confidence: 99%
“…Its metabolism and actions are similar to those of prednisone and prednisolone, but its focused hepatic delivery and low systemic availability have the theoretical advantage of combining precision targeting of the liver with low systemic toxicity. Multiple small single-center clinical experiences have demonstrated that budesonide can improve laboratory findings in treatment-naïve individuals [128][129][130][131], and they have justified the performance of a large randomized clinical trial comparing budesonide combined with azathioprine with a standard prednisone and azathioprine combination [132]. The budesonide combination normalized liver tests more frequently (47% versus 18%) and with fewer side effects (28% versus 53%) than the standard prednisone combination after 6 months [132].…”
Section: Budesonidementioning
confidence: 99%
“…The calcineurin inhibitors (cyclosporine and tacrolimus) [216,217] and the purine antagonist (mycophenolate mofetil) [218] have promise as site-specific drug therapies, and budesonide has been used in combination with azathioprine as an effective frontline regimen with low frequency of side effects [219,220]. These interventions should improve outcomes, and the boundaries of their success must be fully mapped before new studies can accurately address residual deficiencies.…”
Section: Logical Road Map For Future Studiesmentioning
confidence: 99%